2005
DOI: 10.1152/japplphysiol.00075.2004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of AMP kinase in vascular smooth muscle

Abstract: AMP-activated kinase (AMPK) is a highly conserved heterotrimeric kinase that functions as a metabolic master switch to coordinate cellular enzymes involved in carbohydrate and fat metabolism that regulate ATP conservation and synthesis. AMPK is activated by conditions that increase AMP-to-ATP ratio, such as exercise and metabolic stress. In the present study, we probed whether AMPK was expressed in vascular smooth muscle and would be activated by metabolic stress. Endothelium-denuded porcine carotid artery seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 40 publications
12
77
3
Order By: Relevance
“…AMPK was immunoprecipitated with anti-␣1-and anti-␣2-AMPK antibodies prior to AMPK assay. The AMPK catalytic ␣1-subunit isoform accounted for 90% of the total AMPK activity in ASMC lysates (data not shown), confirming results obtained with porcine carotid arteries (29). Treatment with 10 Ϫ7 M vasopressin, angiotensin II, or endothelin-1 led to AMPK activation (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…AMPK was immunoprecipitated with anti-␣1-and anti-␣2-AMPK antibodies prior to AMPK assay. The AMPK catalytic ␣1-subunit isoform accounted for 90% of the total AMPK activity in ASMC lysates (data not shown), confirming results obtained with porcine carotid arteries (29). Treatment with 10 Ϫ7 M vasopressin, angiotensin II, or endothelin-1 led to AMPK activation (Fig.…”
Section: Resultssupporting
confidence: 86%
“…*, significant difference (p Ͻ 0.05, unpaired t test) compared with the controls. stress or anoxia was found to decrease force generation in response to endothelin-1 treatment (29). The underlying mechanisms, which were not investigated, are in line with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, while AICAR causes a small (~12%) vasodilation, neither metformin nor phenformin have an effect and N 2 ‐2DG elicits a vasoconstriction (Rubin et al. 2005). A final consideration is that in our study, neither adiponectin nor the presence of intact PVAT had any effect on calcium signals (Ca 2+ sparks or waves) in intact pressurized arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stretch is also known to activate the AMP-activated protein kinase (AMPK) in muscle cells [12,13]. AMPK is a serine-threonine kinase, which is emerging as an important regulator of diverse cellular pathways in regulating whole-body energy metabolism.…”
Section: mentioning
confidence: 99%
“…A large number of cellular signal transduction pathways can be activated by stretch, such as the JNK, a group of MAPK, PKC, and JAK/STAT pathway [9][10][11]. It has also been suggested that stretch can activate the AMP-activated kinase (AMPK) in muscle cells [12,13].…”
Section: Introductionmentioning
confidence: 99%